Risk Factors for Non-arteritic Anterior Ischemic Optic Neuropathy: A Large Scale Meta-Analysis - Liu, Bing; Yu, Ying; Liu, Wen; Deng, Tuo; Xiang, Daoman (Frontiers in Medicine, 2021)
Objective We conducted a meta-analysis to explore all potential risk factors for nonarteritic anterior ischemic optic neuropathy (NAION) based on published literature. Methods A comprehensive literature search through online databases was performed to obtain studies concerning risk factors of NAION up to June, 2020. Pooled unadjusted odds ratios (ORs) or rate ratios (RRs) were calculated to evaluate the weight of risk factors. This study was registrated in PROSPERO under number CRD42018084960. Results Our meta-analysis included 49 original studies including more than 10 million patients. The following risk factors were proved to be significantly associated with NAION: male gender (OR = 1.67, 95%CI: 1.50-1.85, P < 0.00001), hypertension (RR = 1.28, 95%CI: 1.20-1.37, P < 0.00001), hyperlipidemia (RR = 1.43, 95%CI: 1.26-1.62, P < 0.00001), diabetes mellitus (RR = 1.53, 95%CI: 1.36-1.73, P < 0.00001), coronary heart disease (RR = 1.68, 95%CI: 1.24-2.27, P = 0.0008), sleep apnea (RR = 3.28, 95%CI: 2.08-5.17, P < 0.00001), factor V Leiden heterozygous (RR = 2.21, 95%CI: 1.19-4.09, P = 0.01) and medication history of cardiovascular drugs. Conclusion We concluded that the above risk factors were significantly related to NAION. Better understanding of these risk factors in NAION can help direct therapeutic approaches.